Integrating Digital Competence and Islamic Work Ethics to Enhance Change Readiness: The Mediating Role of Employee Engagement - Indah Rizki Maulia; Nera Marinda Machdar; Yayan Hendayana; Zahara Tussoleha Rony; Joseph M J Renwarin (Al-Qalam Institute, 2026)
Digitalization has become a strategic necessity for Islamic Rural Banks (BPRS) in Indonesia, making employees' readiness for change critical to successful transformation. This study examines the roles of digital competence, Islamic work ethic, and employee engagement in enhancing change readiness, providing insights for strengthening human resource strategies in the digital era. The study was conducted among 200 employees working in Rural Islamic Banks (BPRS) operating across the Greater Jakarta region (Jabodetabek). Respondents were selected using a purposive sampling technique based on predetermined criteria. Data were gathered through a structured questionnaire using a five-point Likert scale and analyzed with SmartPLS 4 to assess the proposed relationships among the research constructs. Digital competence and Islamic work ethic have positive and significant effects on employee engagement and change readiness. Employee engagement has a significant positive effect on change readiness. Also, it serves as a partial mediator in the relationships between digital competence and change readiness, and between Islamic work ethic and change readiness. This study provides empirical evidence that integrating these elements positions organizations better to support successful change initiatives and achieve sustainable organizational development in an increasingly digital environment.